Efficiency of volumetric equations for Manilkara spp. In managed forest in the Eastern Amazon Eficiência de equações volumétricas para Manilkara spp. em floresta manejada na Amazônia Oriental - dos Santos M.F. (2019)
© 2019 Nativa, Sinop. All rights reserved.The objective of this study was to evaluate the efficiency of specific equations for Manilkara spp. in different Annual Production Units (UPA) and in different diametric classes, comparing them with a general equation, in the forest area under management in the Tapajós National Forest, Pará. Four volumetric models were adjusted for the total set of 5.231 sampled trees in order to obtain a representative general equation of the species in the UPAs as well as in the diametrical classes in which the trees were distributed. Then, the selected model was adjusted by UPA and by diameter class, obtaining different specific equations. The Graybill model identity test was applied to compare the equations, and the Chi-square test was used to validate the equations. The specific equations presented superior performance when compared to the general equation for the UPAs and for the diametric classes. In addition, the identity test showed a significant difference between the equations, indicating that it is not statistically adequate to use a single equation for the Manilkara spp. volumetric estimates in all UPAs and in all diametric classes. Therefore, we recommend using specific equations because, in addition to being valid, they can generate more accurate estimations of commercial volumes.